FOSE: a framework for open science evaluation - Walther, Alexander; van den Bosch, Jasper J. (Frontiers in Computational Neuroscience, 2012)
Pre-publication peer review of scientific literature in its present state suffers from a lack of evaluation validity and transparency to the community. Inspired by social networks, we propose a framework for the open exchange of post-publication evaluation to complement the current system. We first formulate a number of necessary conditions that should be met by any design dedicated to perform open scientific evaluation. To introduce our framework, we provide a basic standard and a protocol of its communication thereof. We argue for the superiority of a provider-independent framework over a few isolated implementations which allows the collection and analysis of open evaluation content across a wide range of diverse providers like scientific journals, research institutions, social networks, publishers websites and more. Furthermore, we describe how its technical implementation can be achieved by using existing web standards and technology. Finally, we illustrate this with a set of examples and discuss further potential.